The Cost of Following Traditional Gender Norms: Evidence from a Paid Leave for Seriously Ill Children - Valentina Paredes; Francisca Perez; Francisco J. Pino; Patricia Olmedo Cortés (Institute of Labor Economics (IZA), 2024)
In this paper we exploit the introduction in February 2018 of a new paid parental leave program to care for a seriously ill child in Chile (SANNA) to identify the role of both economic incentives and gender norms on families' decisions regarding market versus home production specialization. To measure the impact of economic incentives, we utilize the design of the SANNA program, which covers the beneficiary's wages up to a specific threshold, beyond which the benefit remains fixed. The efficient allocation of this benefit depends on the income levels of family members and whether their income exceeds the threshold. To investigate the role of gender norms, we compare the effect of economic incentives among older, more traditional families and younger families. Our results indicate that both gender norms and economic incentives affect parental leave allocation. We estimate that older families pay a cost of USD 1,200 for adhering to traditional gender norms compared to younger families.
Keywords: D13; J22; J16; 330; parental childcare; gender identity norms; gender wage gap